A Hardy Type Inequality and Inde Nite Eigenvalue Problems on the Homogeneous Group (Journal of Partial Differential Equations, 2020)
In this paper we present a Hardy type inequality and a Picone type identity for the real sub-Laplacian on the homogeneous group. The existence of the indefinite eigenvalue problem and the simplicity of the principal eigenvalue are proved.
Keywords: Hardy type inequality; Picone type identity; indefinite eigenvalue problem; homogeneous group